Factores psicosociales y procedimiento legal en casos de violencia sexual infantil en Ecuador - Carrión Ramon, Betty Brooke (2022)
In the present research work entitled "Psychosocial factors and legal procedure in child sexual violence victims in Ecuador", the general objective was to analyze the psychosocial factors and legal procedure in child sexual violence cases in Ecuador, verifying the affectation in the short or long term generated by these criminal acts against the minors involved. Also referring to the specific objectives, the psychosocial factors description is verified, and the study of the Legal Procedure in these cases of sexual violence. Within the methodology, the level or research scope was descriptive, the research design is non-experimental, and a semi-structured interview was conducted with law professionals from different institutions, where the qualitative results coincide that the state is guarantor of the best child interests; although due to professional malpractice victimization occurs. As well as, from a quantitative approach, through a meta-analysis of one hundred scientific articles that allowed the classification, determining the physical, psychological and social child victims’ consequences of sexual violence, through inductive - deductive methods that, starting from particular general knowledge, which has allowed to arrive at the conclusions and recommendations.